Physical, Chemical Properties, And Effect Of Storage Condition On Antioxidant Activity Of An Instant Blue Drink From Butterfly Pea Flowers (Clitoria Ternatea) - Mohamed, Suhaila (Universiti Sains Malaysia, 2021)
Butterfly pea flowers (Clitoria ternatea) are rich in nutrients and anthocyanin, which contributes to its antioxidant properties. The utilization of butterfly pea flowers’ natural blue colour as a substitute to synthetic colouring agents which is harmful to human health, could add functional value to food products. Accordingly, this study was conducted to develop and analyse the physical, chemical properties, and effect of storage condition on antioxidant activity of an instant blue drink from butterfly pea flowers. The extraction of butterfly pea flowers was done at 60 oC for 37 min, formulated with xylitol and citric acid (12.3 % and 0.03 % respectively), and freeze-dried at -50 oC / 0.090 mBar for 48 hr. Physical and chemical properties of the instant blue drink including bulk density, colour, pH, proximate composition, and mineral content were analysed. The colour of the instant blue drink was mainly affected by dilution of extract and the addition of citric acid which also subsequently changed its pH. The L* value of instant blue drink showed more than 50 % increment as compared to butterfly pea flowers, while the b* value decrease significantly. The moisture, ash, fat, protein, and crude fibre percentage composition of the instant blue drink is 1.46 ± 0.04 %, 0.13 ± 0.02 %, 1.94 ± 1.32 %, 0.89 ± 0.02 %, and 0.43 ± 0.08 %, respectively. Concurrently, the content of calcium, magnesium, and potassium of the instant blue drink is -0.007 ± 0.002, 0.061 ± 0.002, and 0.195 ± 0.118 mg/g, respectively. The antioxidant activity of the instant blue drink was evaluated after 30 days at four different condition which include two factors, temperature, and light. The optimal storage condition of instant blue drink is at 4 oC with the absence of light. Hence, the physical, chemical, and antioxidant activity of an instant blue drink from butterfly pea flowers (Clitoria ternatea) were successfully analyzed.